WILK IN RUSSIA. SUBALTERN? IN EMPIRE? - Dąbrowski, Mieczysław (Porównania, 2014)
The first part of the article is a polemic with the Polish version of postcolonialism, which adopted the name post-dependence. The author criticizes mimicking the romantic code, abstractness, operating essentialist oppositions which, in the modern meaning of culture processes, are regarded as anachronistic. The second part discusses the works of Mariusz Wilk, who is a voluntary immigrant in Russia, and his writing is treated as a model of sovereign reflection.